Plasmonic Effect on the Magneto-Optical Property of Monolayer WS2 Studied by Polarized-Raman Spectroscopy - Wuguo Liu; Zhongtao Lin; Shibing Tian; Yuan Huang; Huaqing Xue; Ke Zhu; Changzhi Gu; Yang Yang; Junjie Li (Applied Sciences, 2021)
In recent years, the magneto-optical properties of two-dimensional transition metal disulfides have attracted more and more attention due to their further device applications in spintronics and valleytronics. However, to our knowledge, the plasmonic effect on the magneto-optical properties of WS2 has not been studied. In this work, monolayer WS2 transferred on SiO2/Si substrate and Au film were investigated respectively using polarized-Raman spectroscopy at 4 K under different magnetic fields. Prominent magnetic field–induced variations in the Raman intensities of WS2 samples were observed, which also exhibited significant differences in the spectral evolution versus magnetic field. The resonance magnetic field was 5 T and 5.5 T for the WS2 on SiO2/Si substrate and Au film, respectively. Remarkably, the magneto-optical Raman intensities of <semantics><msubsup>A1′</msubsup> </semantics> and 2LA(M) modes for WS2 on Au film were reduced to approximately 60% compared with that of WS2 on SiO2/Si. These results suggest that the plasmonic effect–induced charge transfer plays an important role in the magneto-optical Raman effect of WS2.